Кордон і дім як онтологічні універсалії в українській канадській літературі - Шадріна, Тетяна Володимирівна; Шадрина, Т. В.; Shadrina, T. V. (Миколаїв : Вид-во ЧНУ ім. Петра Могили, 2017)
У статті простежено місце та роль таких універсальних категорій, як дім та кордон, в онтології творів українських письменників-емігрантів першої ґенерації в українсько-канадській літературі. Універсалії дому та кордону в творчості перших українськоканадських авторів співвідносяться з відтворенням процесів, пов’язаних зі зміною фізичної та психічної локації етнічного «дому» переміщених осіб, реактуалізацією культури та традицій на новонабутій батьківщині, поетапною (ре)конструкцією їхньої національної (як також і гендерної, і феміністської) ідентичності. Рефлексія кордону в перших україно-канадських творах передовсім обумовлена травматичним досвідом зміни соціокультурного середовища переселенців, і як наслідок – формуванням концепту бездомності. Попри поступову і неухильну «канадізацію» емігрантів, у творах авторівпіонерів доволі сильно відчутна фольклорна традиція, сформована на батьківщині і перенесена в чужі соціокультурні реалії. В статье прослеживается место и роль таких универсальных категорий, как дом и граница, в онтологии произведений украинских писателей-эмигрантов первого поколения в украинско-канадской литературе. Универсалии дома и границы в творчестве первых украинско-канадских авторов соотносятся c воспроизведением процессов, связанных со сменой физической и психической локации этнического дома перемещенных лиц, реактуализацией культуры и традиций на новообретенной родине, поэтапной (ре)конструкцией их национальной (как и гендерной, и феминистской) идентичности. Рефлексия границы в первых украино-канадских произведениях прежде всего обусловлена травматическим опытом перемены социокультурной среды переселенцев и как следствие – формированием концепта бездомности. Несмотря на постепенную и неизбежную «канадизацию» эмигрантов, в произведениях авторов-пионеров довольно сильно ощущается фольклорная традиция, усвоенная на родине и перенесенная в чужие социокультурные реалии. The article concentrates on the universalias of border and home as defining the concept of identity in Ukrainian-Canadian literature of the pioneering stage. Identity of displaced persons is correlated with their national tradition and culture and, as it is examined and shown, is never fixed (ассording to a postmodernist theory). Gradually it becomes such, which corresponds to the so-called «in-between status». So, the aim of this article is to trace the (re)construction of multiple identities by means of universalias of home and border, which are the central categories for emigrants as we live in the multicultural society when the idea of globalization is «in the air». At the very beginning, Ukrainian emigrants demonstrate haunting anxiety for their stable «home». We deal with poetry, which was the «first word» in Ukrainian-Canadian literature at all. The authors of the initial wave of emigration realize the idea of sorrow (because of the lost home (motherland) and hope for a better future as they obtain freedom and a lot of land in the new country. Universalias of home and border represent spiritual search of the self by the emigrants after crossing the frontier. Another key thesis – to prevent a future generation from assimilation, from forgetting their real home (roots). Two of the most significant novels of the first period of Ukrainian-Canadian literature are Sons of the soil by I. Kiriak and Yellow boots by V. Lysenko which provide an epic picture of Ukrainian emigrants’ life in Canada during the pioneering era. Both authors assert that for displaced persons home corresponds to the feeling of belonging, which is beyond all question connected with land (as the majority of these people are peasants). Their state of un-belonging, nonattachment at last (after many years) changes for home obtaining which conventionally associates with stability. The author of Yellow boots also creates a story of the girl of Ukrainian descending who is in perpetual search for home (her individuality, identity, family), which means fluidity, movement and continuous process of development and exploration.
Граница и дом как онтологические универсалии в украинской канадской литературе
Border and home as ontological universalias in ukrainian-canadian literature
Keywords: Література канадських українців; емігранти; національна ідентичність; дім; кордон; українська канадська література; батьківщина; родина; громада; эмигранты; национальная идентичность; дом; граница; украинская канадская литература; община; emigrants; national identity; home; boundary; Ukrainian-Canadian literature; motherland; family; community